Characteristics and antimicrobial therapy of bloodstream infections in tumour patients with special reference to antibiotic stewardship - Jiri Rejthar; Maximilian Desole; Andrea Stroux; Pierre Kremer; Lars Geerdts; Anna Kopf; Madlen Löbel; Joanna Lasocka; Heidrun Peltroche-Llacsahuanga; Martin Schmidt-Hieber (Journal of Cancer Research and Clinical Oncology)
Abstract Bloodstream infections (BSI) are among the most frequent infections in tumour patients. We analysed 123 tumour patients (105 retrospective, 18 prospective) with BSI. The most common underlying tumour diseases were acute leukaemia/myelodysplastic syndrome (40%), followed by lymphomas (25%) and multiple myeloma (20%). BSI were more frequently caused by Gram-negative than Gram-positive bacteria (53% vs. 40%), including Escherichia coli (33%), coagulase-negative Staphylococcus spp. (14%), and Pseudomonas aeruginosa (10%). The median time to fever resolution was 3 days (range 1–30 days). Neither pathogen type, initial antibiotic treatment, nor key patient characteristics significantly affected fever resolution time. Non-susceptibility of the pathogen to empirical antibiotic treatment was linked to prolonged fever resolution (HR 0.53, 95%-CI 0.28-1.0, p = 0.04). The severity of neutropenia on admission had a significant impact on 60-day survival (HR 2.95, 95%-CI 1.10–7.93, p = 0.03). In contrast, such an effect on survival was not observed by the non-susceptibility of the pathogen to primary empirical antibiotic treatment (HR 2.12, 95%-CI 0.71–6.30, p = 0.18). Non-adherence or questionable adherence to antibiotic stewardship (ABS) recommendations (n = 42, 34%) correlated with delayed fever resolution (median 3 days vs. 4 days; p = 0.04) and was more frequent in retrospectively than in prospectively recorded patients (38% vs. 11%, p = 0.03). Gram-negative bacteria still predominate as BSI agents in tumour patients. Prospective evaluation of anti-infective management may enhance adherence to ABS recommendations.